1992
DOI: 10.1203/00006450-199203000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Histidine-Rich Glycoprotein in Human Colostrum and Milk

Abstract: ABSTRACT. Histidine-rich glycoprotein (HRG) is a 74-kD glycoprotein, originally discovered in plasma, which contains an unusually large amount of histidine (13 mol%) and proline (13 mol%). The specific functions of this protein remain unclear, although it binds (reversibly) transition metal ions such as Cu(I1) and Zn(1I) with high capacity (10-13 equivalent) and moderate to high affinity (h = 0.2-10 pM). Because the bioavailability of Cu (I1) and Zn(I1) ions in human milk is high, we have used specific antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…It was originally isolated from human plasma (Heimburger et al 1972) but its presence has been demonstrated also in platelets and milk (Leung et al 1984;Hutchens et al 1992). Its specific function remains unclear, although several biological roles have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally isolated from human plasma (Heimburger et al 1972) but its presence has been demonstrated also in platelets and milk (Leung et al 1984;Hutchens et al 1992). Its specific function remains unclear, although several biological roles have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma is the major pool of HPRG, but it is also found in infant urine, colostrums, milk, platelets, megakaryocytes and immuno cells such as monocytes and macrophages [58,63,64]. The tissue distribution of mouse HPRG mRNA, investigated by Northern blot analysis performed on total RNA from liver, spleen, thymus, heart, lung, kidney, brain and testis, demonstrated that HPRG mRNA is produced only in the liver [65].…”
Section: Localization Site Of Biosynthesis and Primary Structure mentioning
confidence: 99%
“…Plasma is the major pool of HRG, but it is also found in infant urine, colostrums, and milk (Hutchens et al, 1992;Yip and Hutchens, 1991). The concentration of HRG in plasma is 100-150 mg/L (Heimburger et al, 1972;Lijnen et al, 1981b;Morgan et al, 1978).…”
Section: Localization and Biosynthesismentioning
confidence: 99%